2005
DOI: 10.1590/s0100-40422005000200015
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de modelagem molecular de complexos ferriprotoporfirina-IX e quinolinocarbinolaminas antimaláricas: proposta de um farmacóforo

Abstract: . Quinine and quinidine are well-known 4-quinolinecarbinolamines that exhibit antimalarial activity, but, in contrast, their epimers 9-epiquinine and 9-epiquinidine are almost inactive. Literature data are conflicting in describing the 4-quinolinecarbinolamine interaction mode with the molecular target, the ferriprotoporphyrin IX [Fe(III)PPIX]. In the present paper, a pharmacophore is proposed based on the binding of the nonaromatic nitrogen to the iron atom. The 4-quinolinecarbinolamine antimalarials were sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…Nevertheless, they suggested that covalent complexes might be formed with the ferriprotoporphyrin IX monomer. In a molecular modeling study, da Silva et al 13 proposed that the interaction with ferriprotoporphyrin IX involves the binding of Fe III to the quinuclidinic nitrogen. Hawley et al…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, they suggested that covalent complexes might be formed with the ferriprotoporphyrin IX monomer. In a molecular modeling study, da Silva et al 13 proposed that the interaction with ferriprotoporphyrin IX involves the binding of Fe III to the quinuclidinic nitrogen. Hawley et al…”
Section: Introductionmentioning
confidence: 99%
“…A mefloquina (Figura 8) é uma molécula da série estrutural dos quinolínicos, desenvolvida durante a Guerra do Vietnã para atuar nas cepas de P. falciparum resistentes (Silva, 2005).…”
Section: A Busca De Antimaláricos No Cenário Nacionalunclassified
“…These drugs are generally used to treat malaria due to their low cost, tolerance, safety in the treatment of pregnant women, lack of toxic effect in recommended doses, and high effectiveness in curing the disease. 37,38 Chloroquine-resistant P. falciparum, first detected in 1961 in Vietnam, was reported in several American soldiers, 39 motivating an intensive program of research for antimalarial new agents. Dapsone and pyrimethamine/sulfadoxine were introduced in prophylaxis.…”
Section: Malaria and Leishmaniasis Validated Therapiesmentioning
confidence: 99%